Effect of the timing of presentation of ball course information on kinematics of table tennis forehand and backhand drives - Iino, Y. (Book of abstracts of The 14th ITTF Sports Science Congress and 5th World Racquet Sports Congress, Suzhou, 23-25.04.2015, 2015)
Table tennis players generally have a limited amount of time for making strokes owing to high stroke frequencies. In a match, it is of advantage for a player to make his opponent perceive the course of his own hitting ball as late as possible. The purpose of this study was to determine the effect of the timing when the course information of an approaching ball is provided on the kinematics of table tennis forehand and backhand drives in male collegiate players. Seven Division I and seven division III collegiate players performed the forehand and backhand drives against topspin balls under the two conditions 1) that ball course information was provided for a player before balls were projected by a ball machine (pre) and 2) that ball course was not apparent until balls were projected (late). A motion capture system with 7cameras (Mac3D) was used to collect the 3D coordinate of the markers attached to the participants at 200Hz. In Late condition, participants were asked not to predict ball courses. One stroke which recorded the highest racket speed at impact was selected for each condition. Variables examined were the racket speed at impact, the angles of trunk and pelvis axial rotations, and the timing of beginning of pelvis axial rotation. Two-way repeated measures ANOVA was used to test the effect of the timing (pre vs. late) and the performance level (advanced vs. intermediate) on the variables. There was no interaction of the timing and performance level. There were also no significant differences between the advanced and intermediate players. The racket speed at ball impact was not significantly different between the two conditions for the forehand and backhand drives. For the forehand drive, the pelvis rotation angle at the time of ball projection (about 0.47 s before impact) and the pelvis angle at the completion of the backswing were smaller in the "late" condition than in the "pre" condition, whereas the pelvis rotation angles were not significantly different between the two conditions for the backhand drive. The change in pelvis rotation angle from the backswing completion to ball impact was smaller in the "late" condition than in the "pre" condition for the forehand drive, whereas the change in pelvis rotation angle was similar between the two conditions for the backhand drives. The timing of beginning of pelvis axial rotation was significantly later in the "late" condition than in the "pre" condition for the forehand drive, whereas the timing similar between the two conditions for the backhand drives. The timing of beginning of pelvis rotation and the angles of pelvis axial rotation were significantly affected by the timing of presentation of ball course information for the forehand drive, but not for the backhand drive. This result is seemingly due to that a relatively long time is required for the swing (0.17-0.20 sec for pelvis forward rotation) in the forehand drives.